Efforts to access the potent antitrypanosomal marine natural product janadolide: synthesis of des- tert -butyl janadolide and its biological evaluation - Athawale, Paresh R.; Jachak, Gorakh; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, Srinivasa (ACS Omega, 2018)
To identify novel antitrypanosomal agents based on Janadolide, a potent macrocyclic polyketide–peptide hybrid, a macrolactonization strategy was explored. We prepared des-tert-butyl Janadolide and evaluated its antitrypanosomal activity. Our findings suggest that the tert-butyl group is necessary for the desired bioactivity.

Design, synthesis, and structural analysis of cladosporin-based inhibitors of malaria parasites - Babbar, Palak; Das, Pronay; Manickam, Yogavel; Mankad, Yash; Yadav, Swati; Parvez, Suhel; Sharma, Amit; Reddy, Srinivasa (ACS Infectious Diseases, 2021)
Here we have described a systematic structure activity relationship (SAR) of a set of compounds inspired from cladosporin, a tool compound that targets parasite (Plasmodium falciparum) lysyl tRNA synthetase (KRS). Four sets of analogues, synthesized based on point changes in the chemical scaffold of cladosporin and other logical modifications and hybridizations, were assessed using high throughput enzymatic and parasitic assays along with in vitro pharmacokinetics. Co-crystallization of the most potent compound in our series (CL-2) with PfKRS revealed its structural basis of enzymatic binding and potency. Further, we report that CL-2 has performed better than cladosporin in terms of metabolic stability. It thus represents a new lead for further optimization toward the development of antimalarial drugs. Collectively, along with a lead compound, the series offers insights on how even the slightest chemical modification might play an important role in enhancing or decreasing the potency of a chemical scaffold.